(untitled) (Journal of Information Systems and Technology Management, 2005)
Generally, documental research depends on written bibliographical note cards that help find important text for a given research. However, the manual search for frequently used data such as author, publisher, topic, gets complicated as records increase resulting in a time consuming process that hinders the desired brainstorming. The software here presented solves two main issues: it allows a smoother and quicker data entry, and the flexibility to search by multiple criteria matching information for a specific author, publisher, topic, subtopic and date. The software also eases text transcription and builds the documental references that will be cited on research papers. The software is based on the object oriented (OO) programming philosophy using Microsoft Access as a widely used relational database system.